PERBEDAAN AGAMA DENGAN AKULTURASI TRADISI SUBAK DALAM MEMPENGARUHI PSIKOLOGIS, KARAKTER, DAN PERILAKU MASYARAKAT - Kadek Ari Setia Utama Putra; Kadek Ari Anggarini; Putu Pande Pinandia Eka Putri; Ni Komang Sutriyanti (Pangkaja: Jurnal Agama Hindu, 2021)
Bali is inseparable from its culture and local wisdom which is combined with the culture of other religious communities, one of which is the acculturation of Subak culture carried out by Hindus and Muslims. Various things happened in Indonesia regarding the incidence of diversity intolerance, so that the community formed a community organization in Bali that regulates water for rice fields from a water source in an area whose members consist of a combination of Hindus and Muslims living in rural areas. This organization was formed by the community to maintain community harmony and was used as a forum for forming cultural acculturation. The maintenance of the Subak cultural acculturation carried out in Yeh Embang Village, Mendoyo, Jembrana is able to change the psychology of the community in influencing the character and behavior of the community. The objectives to be achieved in this study are to describe the existence of Subak culture in today's modern era, to analyze the process of cultural acculturation between Hindus and Muslims in Subak Yeh Santang, and to analyze the impact of acculturation of Subak culture between Hindus and Muslims on the psychological and character of society. The research instruments include interviews, questionnaires, documentation, objects of observation and books and journals. The data obtained were analyzed using qualitative descriptive methods. The results of this study are as follows; Acculturation of Subak culture can strengthen harmony between residents or the community and there is a positive impact of acculturation of Subak culture on the psychology, mindset, and behavior of the community which affects the character of the community in a better direction with a percentage of the influence of Subak cultural acculturation on the psychology of society by 87% and the role of the community 78.11% indicates that the community plays a very important role in the implementation of this cultural acculturation.